"A new consciousness of the countryside"? Elite ruralism in contemporary China. Issue 1 (2nd January 2019) - Cody, Sacha
Abstract: This article discusses an elite form of ruralism in contemporary China. Using ethnographic material collected at two sustainable farming events, it introduces the intellectuals who organize these events as well as the urban residents who attend. Ruralism—the idea that 'real' China is found in the countryside, not the city—legitimates intellectuals' narrative of Chinese nationhood as modern yet in touch with its cultural heritage and offers the promise of rediscovery and starting afresh to urban attendees, the majority of whom were born in the countryside. While elite ruralism sidesteps engaging rural residents and raises questions of representation, it also illuminates processes of demographic pluralization in the Chinese countryside, a trend observable elsewhere in Asia.